Movimentos da ABEM para a educação musical no Brasil: imaginários sociais em construção pelas narrativas de presidentes - Schwan, Ivan Carlos (2021)
This thesis is linked to the Education and Arts Research Area (LP4) of the Graduate Program in Education at the Federal University of Santa Maria (UFSM) and incorporates studies of the research group "FAPEM: formation, action and research in music education". Its main objective was to understand movements, memories and history, instituted and instituting ABEM as an institution that enhances Brazilian Music Education, through the imaginary significations built in the narratives of its presidents. Its specific objectives sought to understand the Association's memory for the construction of a history of its trajectory, through the knowledge present in the presidents' narratives, memories and recollections; understand how ABEM has intensified and constituted movements and proposals in relation to the Brazilian Music Education, highlighting the consolidation of postgraduate studies, music education in Basic Education, and specialized music schools, the production and dissemination of scientific publications and the construction of a collective identity on Brazilian Music Education; analyze what the presidents consider as aspects of the Association's political representation, promoter factors that guide the organization of thought processes, planning, and implementation of institutional proposals. Thus, Bibliographic Research (LIMA; MIOTO, 2007) and Narrative Biographical Investigation (SOUZA, 2014), and approaches with the Social Imaginary Theory (CASTORIADIS, 1982), were used as the basis for the analysis and interpretation of data, and deep theoretical understanding. Seven (07) presidents of ABEM participated in this the investigation, through narrative interviews, from its foundation to the present time (1991-2019). From this setting, a thesis of live, imaginary narratives of the presidents was constructed. It legitimizes the Brazilian Association of Music Education, as a place of recognition and collective representation, which through its instituted and instituting movements, emphasize the Brazilian Music Education, contributing for the consolidation and organization of an area of knowledge for research, production and scientific dissemination, for Basic Education, for undergraduate and graduate courses in Music and Education, for the promotion of national public policies for Basic Education and also in the development of international policies. It is noteworthy to highlight that this research sought to contribute to the thinking process about the social imaginary significations and their movements and memories of stories narrated by ABEM, by its presidents, to the Brazilian Music Education. It also enhanced the perception of the construction of the Institution's political representation, its organizational areas, and the implementation of institutional proposals. The thesis organizes the existence of 30 years of ABEM as an institution that was created through instituted and instituting movements, led by presidents and their directors, showing a scientific community that is consolidated.